Uji Angka Lempeng Total dan Kontaminan Koliform pada Susu Kedelai Bermerek yang Beredar di Kota Denpasar - Theofanny, Michael Jordi; Gunam, Ida Bagus Wayan; Suwariani, Ni Putu (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2021)
This research aimed to testing total plate count and coliform contaminant o n l egal product soy milk sold in Denpasar city is qualified to Indonesian National Standard (SNI) and safe to consumption. Soy milk has high nutrition and good for growth microorganisms. Microorganisms in soy milk is good for health but be worried have a dangerous microorganisms. Samples of soy milk based on purposive method , tested with total plate count agar with pour plate method and contaminant coliform with most probable number method . The result of testing total plate count, all samples is under maximum of SNI  5 × 10 4 CFU /g. After that soy milk sample t esting of coliform contaminant, the result is all samples has negative coliform contaminant. Conclusion of the research is all of the legal product soy milk sold in Denpasar qualified to SNI No. 01-3830-1995 and safe to consumption. Keyword: coliform, Denpasar city, Indonesian national standard, soy milk, total plate count.